2008
DOI: 10.1111/j.1467-839x.2008.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese working in groups: Effort dispensability versus normative influence

Abstract: Chinese participants were found less likely to social loaf when working in groups than did North Americans. This result was attributed mainly to the collectivism and individualism characterizing Chinese and North Americans, respectively. However, this explanation does not address how Chinese people's social loafing tendency may vary across situations. If Chinese participants are concerned about their relations with coworkers, they should be more likely to conform to the performance level of their coworkers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Americans, who value individualism, prefer to work alone rather than as part of a team (Hernandez & Iyengar, ), and, unlike Chinese, they feel more accountable for their work outcomes when working alone than when working as part of a team (Gelfand et al, ). Our finding is consistent with that of previous research, demonstrating that social loafing, which pertains to the lower level of performance of individuals when working as part of a team versus working alone, is more prevalent in individualistic cultures than in collectivistic cultures (Earley, ; Erez & Somech, ; Hong et al, ). However, the American's level of originality remained as high in the presence of their peers as it was under a supervisor or when working alone, because the presence of others did not signal to them the need to conform to normative ideas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Americans, who value individualism, prefer to work alone rather than as part of a team (Hernandez & Iyengar, ), and, unlike Chinese, they feel more accountable for their work outcomes when working alone than when working as part of a team (Gelfand et al, ). Our finding is consistent with that of previous research, demonstrating that social loafing, which pertains to the lower level of performance of individuals when working as part of a team versus working alone, is more prevalent in individualistic cultures than in collectivistic cultures (Earley, ; Erez & Somech, ; Hong et al, ). However, the American's level of originality remained as high in the presence of their peers as it was under a supervisor or when working alone, because the presence of others did not signal to them the need to conform to normative ideas.…”
Section: Discussionsupporting
confidence: 92%
“…In these collectivist cultures, the group is held accountable to the organization and supervisors (Chen, Meindl, & Hui, ; Gelfand et al, ). Social loafing was not found with the Chinese, who adjusted their performance to conform to the group norms (Earley, ; Hong, Wyer, & Fong, ; Liu, Friedman, & Hong, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In general, people from Eastern (i.e., collectivistic) cultures are less prone to loafing than are people from Western (i.e., individualistic) cultures (Karau & Williams, 1993). Moreover, there is evidence that Chinese participants socially loaf under different conditions than do Western participants (Ying-yi, Wyer, & Fong, 2008). Thus, future studies should consider the effects of individualistic versus collectivistic orientations on problem identification in team contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al (2008) found that collectivist Chinese are less likely to social loaf than individualistic American. Jassawalla et al (2009) demonstrated that international students from collectivist cultures were not immune to SL.…”
Section: Social Loafing and Collectivismmentioning
confidence: 99%